A STUDY ON THE ROLE OF FINANCIAL INSTITUTION INPROMOTINGENTREPRENEURSHIP IN SMALL ANDMEDIUM ENTERPRISES WITH REFERENCE TOBANGALORE - Theamozhi, Sagaya; Amaladas, Augustin (European Scientific Journal, ESJ, 2014)
Small and Medium Enterprises is defined on the basis of their charactertics, that includes size of the capital, investment, number of employees, turnover, management behavior, location and market share but very commonly used characteristics is number of employees in the enterprise. Since Bangalore is a developing city here Small Scale Enterprise means a firm employing less than 50 workers and medium size enterprise would usually mean those that have 50-99 workers.SME‘s has also considered as a subject of discussions in many workshops and seminars locally and internationally. Government also plays a major role in various levels like local, state, and federal levels in formulating new policies with an aim of empowering, encouraging, and facilitating growth and development and performance of the SME‘s, even others institutions also focus on assisting the SME‘s to grow through soft loans and other fiscal incentives.The financial institution has been developed to support SME‘s on both theoretical and empirical grounds. It also inherent the weakness of SME‘s in accessing the financial services. Till today, the role of financial institution in developing SME‘s has been in satisfactory level and encouraging, but the dynamic of the present SME‘s focus the institution and banks for its further improvement in their performance. In this direction and attempt has been made to find the areas of improvement in performance and to suggest concrete ideas to this project.